CaMKII: cardiac physiological functions - Valverde, Carlos Alfredo (2023)
Calcium-calmodulin-dependent protein kinase (CaMKII) is a Ser/Thr kinase whose activity is triggered by calcium (Ca2+), in response to various distinct signaling pathways in different organs, including the pancreas, liver, brain, and heart. CaMKII was discovered in the late sixties. Interestingly, the initial mentions of this kinase were nearly simultaneous in both the brain and the heart, despite it is more abundant in the brain, where it plays a crucial role in memory and learning processes. CaMKII is unique in that it is very widely distributed and can phosphorylate a broad range of proteins. These properties promptly suggested that CaMKII regulates many physiological responses to agonists that elevate intracellular Ca2+, leading to its designation as the "multifunctional Ca/CaM-dependent protein kinase" or "CaM-dependent multiprotein kinase". Encoded by four different genes (α, β, γ, and δ), CaMKIIδ is the predominant isoform in the heart, with two splice variants in the adult myocardium: δB, mainly localized in the nucleus, and δC, primarily found in the cytosol. Given its role in phosphorylating proteins related to Ca2+ handling and excitation-contraction coupling (ECC), CaMKII is believed to play an important role in physiological processes. However, unlike its well-established role in memory and learning, the physiological significance of CaMKII on cardiac function is less acknowledged. Indeed, its better-known associations lie in non-physiological actions within the heart, particularly in various cardiac pathologies such as heart failure (HF), myocardial infarction, and cardiomyopathies, leading to contractile dysfunction and malignant arrhythmias. This mini review aims to provide a concise summary of CaMKII's role on cardiac physiology.